Anisotropic hair keratin-dopamine composite scaffolds exhibit strain-stiffening properties - Zhao, Zhitong (2021)
Human hair keratin (HHK) has been successfully explored as raw materials for three-dimensional scaffolds for soft tissue regeneration due to its excellent biocompatibility and bioactivity. However, none of the reported HHK based scaffolds is able to replicate the strain-stiffening capacity of living tissues when responding to large deformations. In the present study, strain-stiffening property was achieved in scaffolds fabricated from HHK via a synergistic effect of well-defined, aligned microstructure and chemical crosslinking. Directed ice-templating method was used to fabricate HHK-based scaffolds with highly aligned (anisotropic) microstructure while oxidized dopamine (ODA) was used to crosslink covalently to HHKs. The resultant HHK-ODA scaffolds exhibited strain-stiffening behaviour characterized by the increased gradient of the stress-strain curve after the yield point. Both ultimate tensile strength and the elongation at break were enhanced significantly (~700 kPa, ~170 %) in comparison to that of HHK scaffolds lacking of aligned microstructure or ODA crosslinking. In vitro cell culture studies indicated that HHK-ODA scaffolds successfully supported human dermal fibroblasts (HDFs) adhesion, spreading and proliferation. Moreover, anisotropic HHK-ODA scaffolds guided cell growth in alignment with the defined microstructure as shown by the highly organized cytoskeletal networks and nuclei distribution. The findings suggest that HHK-ODA scaffolds, with strain-stiffening properties, biocompatibility and bioactivity, have the potential to be applied as biomimetic matrices for soft tissue regeneration.